1991
DOI: 10.1128/aem.57.5.1478-1484.1991
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cell Wall-Degrading Enzymes by the Phytopathogenic Fungus Sclerotinia sclerotiorum

Abstract: The range of polysaccharide-degrading enzymes and glycosidases formed by the phytopathogenic fungus Sclerotinia sclerotiorum was monitored following growth on 16 carbohydrate substrates. Endoand exoenzymes capable of degrading cellulosic, hemicellulosic, and pectinolytic polysaccharides were secreted. Pectinolytic activities were produced constitutively on all of the substrates tested. Cellulolytic enzymes were not induced in simple sugar (i.e., glucose or xylose) media. Polysaccharide growth substrates and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(62 citation statements)
references
References 25 publications
0
60
0
2
Order By: Relevance
“…During the interaction with its host, S. sclerotiorum secretes a full complement of CWDEs that can facilitate penetration, macerate tissues and degrade plant cell-wall components (Table 1) (Hancock, 1966;Lumsden, 1969;Riou et al, 1991). Pectin is a major constituent of the plant cell wall and pectinases produced by S. sclerotiorum play a role in pectin degradation.…”
Section: Cell-wall-degrading Enzymesmentioning
confidence: 99%
“…During the interaction with its host, S. sclerotiorum secretes a full complement of CWDEs that can facilitate penetration, macerate tissues and degrade plant cell-wall components (Table 1) (Hancock, 1966;Lumsden, 1969;Riou et al, 1991). Pectin is a major constituent of the plant cell wall and pectinases produced by S. sclerotiorum play a role in pectin degradation.…”
Section: Cell-wall-degrading Enzymesmentioning
confidence: 99%
“…Sclerotinia sclerotiorum is a plant pathogenic ascomycete that attacks a wide range of host species. Biochemical analyses have shown that during the interaction with its host, S. sclerotiorum secretes a complete set of cell wall degrading enzymes [4] that macerate the host tissues and provide nutrients for mycelial growth. During growth on pectic polymers, several endo-and exo-enzymes are sequentially secreted [5].…”
Section: Introductionmentioning
confidence: 99%
“…Oxalic acid evokes the activities of many cell walldegrading enzymes such as polygalacturonases (Riou et al 1991) and it also damages cell walls by chelating Ca 2+ and acidification of host cells (Bateman and Beer 1965). The previous study showed that there is a direct relationship between PAL activity and deposition of lignin (Zhao et al 2007).…”
Section: Discussionmentioning
confidence: 99%